Comparative Delivery of 1,8-Cineole and Eucalyptus Oil Using Chitosan Nanoparticles and PVA Nanofibers: A Polymeric Nanotechnology Toolbox for Antibacterial, Wound-Healing, and Anticancer Applications - Shetta, Amro AbdelAzeem (AUC Knowledge Fountain, 2026)
Bacterial infections remain a major cause of morbidity and mortality and are strongly associated with chronic non-healing wounds through sustained inflammation, high microbial burden, and biofilm-mediated persistence. Importantly, when inflammation and infection become chronic, they can also contribute to carcinogenesis: long-standing immune activation, oxidative stress, and repeated cycles of tissue injury and repair can promote DNA damage, dysregulated signaling, and a microenvironment that supports malignant transformation and tumor progression. In parallel, cancers that arise or progress within inflammatory or infection-associated settings much like chronically infected wounds are often challenging to treat with conventional therapies, which may be limited by systemic toxicity, poor selectivity, recurrence, and the development of resistance. These challenges have renewed interest in natural essential oils and their key terpenoid molecules as multi-target bioactives, yet clinical translation is frequently constrained by volatility, hydrophobicity, and (for whole oils) compositional variability unless robust delivery systems are applied. To address this gap, this thesis investigates a two-level comparative design, (i) a single defined molecule, 1,8-cineole (CIN), versus a compositionally diverse eucalyptus oil (EU), and (ii) one-barrier delivery (direct loading into a polymer matrix) versus a two-barrier architecture (NP-in-NF dual encapsulation) intended to strengthen retention and control diffusion at the biological interface. Chitosan nanoparticles (CS NPs) directly loaded electrospun poly(vinyl alcohol) nanofibers (PVA NFs), and NP-in-NF composite nanofibers (PVA–CS NFs containing bioactive-loaded CS NPs) were formulated and optimized using Box–Behnken designs at both the nanoparticle and electrospinning levels. For CS NP preparation, CS concentration, TPP concentration, and the CIN/CS ratio were systematically optimized to achieve higher loading capacity and improved nanoparticle stability. In parallel, electrospinning optimization identified 9representative conditions of 0.5 mL·h⁻¹ flow rate, 22 kV applied voltage, and 5 mg·mL⁻¹ NP loading, which were then fixed across formulations to enable controlled comparisons. Physicochemical characterization (FTIR, SEM/TEM, size and zeta potential, wettability, TGA/DTG, XRD, and tensile testing), together with release profiling and kinetic modeling (including Weibull-type behavior), confirmed successful incorporation and showed that dual encapsulation increased interaction-stabilization and reduced burst-type exposure, supporting sustained availability up to 72 h at pH 7.4. Antioxidant performance (evaluated in the NP system) depended on the presence of the loaded bioactive. Notably, there was no significant difference between CS-CIN NPs and CS-EU NPs, whereas both bioactive-loaded systems exhibited significantly higher antioxidant-associated responses than blank CS NPs. Antibacterial activity against wound-relevant strains (E. coli, P. aeruginosa, S. aureus, and MRSA) was strain- and encapsulation-dependent: at the NP level, encapsulating CIN or EU into CS NPs consistently improved potency versus blank CS NPs (lower IC50), with CS–CIN NPs showing their strongest effect against E. coli and CS–EU NPs showing the greatest gain against MRSA; at the dressing level, inhibition-zone results indicated that the NP- in-NF two-barrier format (PVA–CS–CIN NFs) provided the most consistent broad-spectrum activity, with the strongest inhibition observed against P. aeruginosa, supporting sustained local delivery as a key driver of application-relevant antibacterial performance. Biocompatibility against L929 fibroblasts remained high (≥ 97% viability across mats), while dual systems enhanced proliferation (up to 117.9% for PVA–CS–CIN) and accelerated scratch closure, achieving near-complete closure at 48 h. In vivo, wound contraction approached near-complete closure by day 10 and reached 100% by day 15, accompanied by improved epithelialization and collagen deposition, again favoring the dual CIN nanofiber system. Finally, anticancer evaluation of the optimized CS- 10CIN NP system at 72 h demonstrated a pronounced potency enhancement versus free CIN across HepG2, MCF-7, HCT-116, Caco-2, HeLa, and AGS cells (e.g., IC₅₀ = 17.25 µg/mL for HepG2 and 28.53 µg/mL for MCF-7), with HepG2 emerging as the most responsive line; docking and thermodynamic descriptors supported multi-target binding patterns consistent with the observed time-dependent effects. Overall, the findings deliver a proof-of-concept structure–property–function message: CIN generally provides more reproducible performance than EU under matched processing, the NP-in-NF two-barrier architecture most effectively converts volatile bioactivity into sustained antibacterial and wound-healing outcomes, and CS–CIN NPs provide the strongest anticancer response within the tested panel.